Beliefs and Anxiety Levels Regarding Available COVID-19 Vaccine among Taif City Population, Saudi Arabia - Mubaraki, MD, Adnan A; AlEssa, Huda A; Almashyakhi, Safa K; Alwagdani, Razan F; Almalki, Nada A; Alrabie, Aeshah D (International Journal of Innovative Research in Medical Science, 2021)
Background: The development of a COVID-19 vaccine is seen as a critical strategy for bringing the pandemic to an end. Understanding the main determinants that influence the community's preferences and demands for a potential vaccine may aid in the development of strategies to improve the global vaccination program. Methods: This is a cross-sectional online self-administered questionnaire study that was distributed in Taif city, Saudi Arabia between March 2021 to June 2021. The survey included socio-demographic data, beliefs toward COVID-19 vaccination, barriers associated with acceptance of COVID-19 vaccination and the last part about generalized anxiety disorder scale. Results: It was reported that 25.6% of the participants had taken at least one dose of the COVID-19 vaccine (COV), and 39.8% are planning to take it. Regarding beliefs and perceptions related to COV, 44.3% had demonstrated positive beliefs and 55.7% had negative beliefs. The analysis showed that 59.7% agreed that COV is safe, and 57.8% believed that it is effective. It was found that 53.3% of the participants were concerned about the vaccine's side effects, and only 9.8% believed that the COVID-19 vaccination is a conspiracy. When we assessed the relationship of attitudes with sociodemographic characteristics of the participants, males, Saudi nationality, singles, higher qualifications, unemployment, and students showed more positive attitudes than the rest. Conclusion: Our research findings show that there is an association between planning to take the vaccine and positive attitudes toward vaccine safety and effectiveness among the Taif City population These results could help the government, ministry of health, health practitioners, and other health organizations to more accurately tailor messages around COVID-19 vaccine programs.